Impaired Lung Homeostasis in Neonatal Mice Exposed to Cigarette Smoke - McGrath-Morrow, Sharon (American Thoracic Society, 2008)
In infants, smoke exposure is associated with more respiratory illnesses and decreased lung function. We hypothesized that perinatal lung is particularly susceptible to the damaging effects of cigarette smoke (CS) and that exposure to CS during this period may alter expression of immune response genes and adversely affect lung growth. To test this, we exposed neonatal mice to 14 days of CS. Immediately after exposure to CS, pulmonary gene expression profiling was performed on 2-week-old CS-exposed lung and age-matched control lung. Nitrotyrosine, TUNEL, MAC3, and phospho-SMAD-2 (p-SMAD2) staining was also performed. At 8 weeks of age, lung volume measurements were determined and mean linear intercept measurements were calculated. Pulmonary gene expression profiling revealed that CS exposure significantly inhibited type 1 and type 2 interferon pathway genes in neonatal lung, compared with age-matched control lung. Neonatal CS-exposed lung also had a significant increase in n-tyrosine, TUNEL, and p-SMAD2 staining when compared with adult CS-exposed lung and age-matched control lung. Lung volumes at 8 weeks of age were modestly but significantly decreased in mice exposed to CS in the neonatal period compared with age-matched controls, consistent with impaired lung growth. The results of this study indicate that exposure to CS during the neonatal period inhibits expression of genes involved in innate immunity and mildly impairs postnatal lung growth. These findings may in part explain the increased incidence of respiratory symptoms in infants and children exposed to CS.